Correction: Reconstructing prehistoric lifeways using multi-Isotope analyses of human enamel, dentine, and bone from Legaire Sur, Spain. - PLOS One Staff (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0316387.].